Adsorptive removal of Pb2+ ions using stable imine linked covalent organic frameworks: A simulated and experimental studies - H. Shanavaz; S. Archana; M.K. Prashanth; K. Yogesh Kumar; V.S. Anusuya Devi; S.B. Benaka Prasad; Fahd Alharethy; Byong-Hun Jeon; M.S. Raghu (Applied Surface Science Advances, 2023)
Porous organic frameworks that are bound covalently are eye-catching materials in the current research. The present work describes the solvothermal synthesis of a combination of 3,3′,5,5′-tetramethyl-[1,1′-biphenyl] 4,4′-diamine and benzene-1,3,5-tricarbaldehyde through covalent bonding to generate TBBT-covalent organic framework (TBBT-COF). The structural, morphological, and computational characterizations confirm the formation of COF. TBBT-COF has been used as an adsorbent for the removal of Pb2+ ions from aqueous media. The effects of pH, initial metal ion concentration, competing ions, and adsorbent dosage were optimized to attain maximum adsorption of Pb2+. The kinetics follow pseudo-second-order and govern the chemisorption of Pb2+ with the imine group of TBBT-COF. The X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) analyses of TBBT-COF after adsorption of Pb2+ support the chemisorption of Pb2+with TBBT-COF. The 2D contour and 3D surface response plots were used to assess the specific and comparative effects of the experimental variables. An analysis of variance (ANOVA) of the regression model was used to establish the relevance of the primary influencing variables on the adsorption of Pb2+over TBBT-COF. It was found to remove 99 % of Pb2+ in 90 min. The results of the real-sample analysis show the efficient removal of Pb2+ even in the presence of other cations. The statistical analysis of the adsorption has been conducted, which indicates the suggested models closely match the experimental data. The high surface area, covalency, and stability of TBBT-COF show its good adsorbent properties.